Preparation method of novel transverse 3D / quasi-2D perovskite heterojunction
By migrating large-volume organic cations under light and electric field treatment, the transverse heterojunction of perovskite thin films was prepared, which solved the problem of difficult preparation of sharp interface heterojunctions in the prior art and improved the stability and photoelectric properties of perovskite materials.
Patent Information
- Application Number
- CN202510210492.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2026-08-25
AI Technical Summary
Existing technologies make it difficult to easily prepare perovskite lateral heterojunctions with sharp interfaces, especially 3D/quasi-2D perovskite heterojunctions, and large-volume organic cations usually do not undergo ion migration in perovskite materials.
A clear and sharp 3D/quasi-2D perovskite heterostructure was formed by directional migration of large-volume organic cations (LOCs) in perovskite thin films under illumination and electric field conditions using a one-step in-situ preparation method.
A 3D/quasi-2D perovskite heterojunction with an ultra-narrow interface was fabricated, which simplified the fabrication process, improved the stability and optoelectronic properties of perovskite materials, and enabled high-efficiency, long-life optoelectronic devices.
Smart Images

Figure CN122641244A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of perovskite material optoelectronic device technology, and particularly relates to a novel method for preparing lateral 3D / quasi-2D perovskite heterojunctions. Background Technology
[0002] Lateral perovskite heterostructures (LPHs) are heterostructures formed by integrating two or more different perovskite materials laterally. A key characteristic of LPHs is that the different perovskite materials share the same substrate. This integration allows electrons and holes to transport laterally between the different materials, resulting in unique optoelectronic properties. In LPHs, the interface between the different perovskite materials plays a crucial role. By precisely controlling the chemical composition and crystal structure of the interface, efficient carrier injection, transport, and recombination can be achieved, thereby optimizing device performance.
[0003] Currently, the main methods for preparing perovskite dimensional heterojunctions (LPHs) include solution ion exchange, gas-phase reaction, and solid-phase reaction, which introduce long-chain organic ammonium ions onto the surface of three-dimensional perovskites to generate two-dimensional and quasi-two-dimensional structures. However, due to limitations in the preparation methods, most perovskite dimensional heterojunctions are vertical heterojunctions, meaning the junction interface is perpendicular to the substrate. The simplified preparation of perovskite lateral heterojunctions has always been a challenge in the field. Furthermore, the formation of microscopic LPHs with sharp interfaces (i.e., "narrow interfaces") remains a technical hurdle.
[0004] As is well known to those skilled in the art, in ABX3 metal halide perovskites, the halide ion at the X-position and the cation at the A-position have low ion migration activation energies and are prone to migration upon external stimulation. Due to the significant steric hindrance of bulky organic cations (LOCs), LOCs are generally considered not to initiate ion migration processes in perovskite materials and are often used as ion migration inhibitors in the field of perovskite quantum dots.
[0005] Our team has discovered that large-volume organic cations (LOCs) can undergo ion migration under specific conditions and promote the formation of transverse perovskite heterostructures with sharp interfaces. This is of great significance for improving the stability of perovskite materials and realizing high-efficiency, long-life perovskite optoelectronic devices, and therefore needs further improvement. Summary of the Invention
[0006] This invention proposes a novel method for preparing lateral 3D / quasi-2D perovskite heterostructures. This method utilizes the ability of bulk organic cations (LOCs) to migrate under specific conditions, promoting the formation of lateral perovskite heterostructures with sharp interfaces, thus obtaining a completely new method for preparing LPHs that differs from existing technologies.
[0007] To achieve the above objectives, the technical solution adopted by this invention is: a novel method for preparing lateral 3D / quasi-2D perovskite heterojunctions, comprising the following steps:
[0008] Step S1: Spin-coat the perovskite precursor solution onto the substrate to form a film, and then place it on a hot stage for annealing and crystallization to form a quasi-two-dimensional perovskite thin film.
[0009] Step S2: Place the quasi-two-dimensional perovskite film between two metal electrodes, which are connected to an external power source as positive and negative electrodes to construct an electric field.
[0010] Step S3: The quasi-two-dimensional perovskite film is placed in an electric field with a strength of 0.1-100V / μm and subjected to light irradiation. Under the simultaneous stimulation of light and electricity, the large-volume organic cations (LOCs) migrate along the direction of the electric field and promote the formation of lateral 3D / quasi-2D perovskite heterostructures.
[0011] The chemical formula of the perovskite precursor solution is L m A n-1 M n X 3n+1 ;
[0012] Wherein, L is a monovalent (m=2) or divalent (m=1) long-chain organic cation;
[0013] A can be methylammonium (MA+), formamidinium (FA+), or cesium ion (Cs+);
[0014] M is a divalent cation of Group IV; for example, lead (Pb2+) or tin (Sn2+) ions.
[0015] X represents CI - ,Br - and I - At least one of them;
[0016] n represents the [MX6] interval between long-chain organic cations. 4- The number of layers of the octahedron, where n = 1 to ∞.
[0017] In the above description, the two metal electrodes may be located on the same side of the quasi-two-dimensional perovskite film or on opposite sides of the quasi-two-dimensional perovskite film. Regardless of the device structure used, it does not affect the achievement of the purpose of this invention, and both should be included within the scope of protection of this invention.
[0018] Furthermore, the illumination conditions in step S3 are as follows: the wavelength of the light source is selected to be smaller than the position of the first exciton absorption peak of the perovskite; the power density of the light source is 1-5000 mW / cm³. 2 .
[0019] Furthermore, in step S3, the quasi-two-dimensional perovskite film is placed in an electric field for at least 10 minutes; and the light treatment lasts for at least 10 minutes.
[0020] Furthermore, the light source type for the illumination processing in step 3 is one of the following: laser, mercury lamp, xenon lamp, or LED.
[0021] Furthermore, the electric field strength in step 3 is 1.5 V / μm; the excitation wavelength of the light source for the illumination treatment is 405 nm, and the power density of the light source is 100 mW / cm². 2 .
[0022] Furthermore, the substrate in step 1 includes one of quartz, PEDOT:PSS, and PVK.
[0023] Furthermore, the long-chain organic cation includes one of the following: decaalkylammonium cation, dodecylammonium cation, tetradecylammonium cation, octadecylammonium cation, phenethylammonium cation, phenylbutylammonium cation, and butylammonium cation.
[0024] Furthermore, the 3D / quasi-2D perovskite heterojunction has a clear and sharp junction interface with a width of less than 10 nm.
[0025] Furthermore, the preparation method is a one-step in-situ preparation method under light and electric field treatment conditions.
[0026] Furthermore, under illumination and electric field conditions, the LOCs in the quasi-two-dimensional perovskite film did not undergo deprotonation, and the formation of 3D / quasi-2D perovskite lateral heterojunctions was solely due to LOC migration.
[0027] The beneficial effects of this invention are:
[0028] (1) This invention focuses on the study of the slowly moving PL decay interface appearing in quasi-two-dimensional perovskite thin film lateral devices under illumination and bias. It discovers the dimensional fusion phenomenon in quasi-two-dimensional perovskites caused by the directional migration of L-site organic ammonium ions, and fabricates 3D / quasi-2D perovskite lateral heterojunctions with ultra-narrow nodal interfaces. We explore the universality of the LOC migration phenomenon in perovskite thin films of different systems.
[0029] (2) The migration interface of the product prepared by this invention is clearly visible in the AFM and SEM morphology results, and the interface width is very narrow. Cross-sectional TEM results confirm that a 3D / quasi-2D heterojunction structure is formed at the migration interface. The quasi-two-dimensional perovskite nanosheets in the migration region fuse to form a high-quality three-dimensional cubic α-CsPbBr3 single crystal, and its transition region is very narrow, with a width of only 9.7 nm, which is the lowest value among existing perovskite dimensional heterojunctions, indicating that the heterojunction has extremely high quality. At the same time, this invention confirms the migration phenomenon of LOCs in the quasi-two-dimensional perovskite film and eliminates the possibility of electrochemical decomposition of ammonium ions.
[0030] (3) The preparation method of the present invention is simple. It can be prepared in situ in one step with only light and electric field treatment, which greatly simplifies the existing preparation method of perovskite dimensional heterojunction. Attached Figure Description
[0031] Figure 1 This is a schematic diagram of the perovskite lateral device structure prepared in Example 1;
[0032] Figure 2 UV-Vis images were obtained for the quasi-two-dimensional perovskite thin film prepared in Comparative Example 1. Figure 2 a) and steady-state PL characterization diagram ( Figure 2 b);
[0033] Figure 3 AFM morphology image of the quasi-two-dimensional perovskite film prepared for Comparative Example 1 ( Figure 3 a) and cross-sectional TEM images of quasi-two-dimensional perovskite lateral devices ( Figure 3 b);
[0034] Figure 4 The images show the PL (potential degradation) over time of the perovskite lateral device of Example 1 under illumination and electric field. "+" and "-" indicate the positive and negative electrodes to which the voltage was applied, with a distance of 80 μm between them. (a) shows the PL over 0–3 s of illumination and voltage application; (b) shows the PL over 5 s–30 min of application. Two independent PL decay interfaces moving from the positive to the negative electrode are observed in the perovskite film.
[0035] Figure 5 The image shows a micro-fluorescence image of the migration interface of the perovskite lateral device in Example 1 after 30 minutes of illumination and bias voltage (a), and a single-point micro-area PL spectrum of the reference sample, the migration region, and the normal region after normalization (b).
[0036] Figure 6The images show: (a) a cross-sectional STEM image of the 3D / quasi-2D perovskite lateral heterojunction interface of the perovskite lateral device in Example 1; (b) a high-resolution cross-sectional STEM image of the 3D perovskite grains in the migration region; and (c) a high-resolution cross-sectional STEM image of the quasi-two-dimensional perovskite nanosheets in the normal region.
[0037] Figure 7 (a) shows the XPS N1s spectra of PBA-CsPbBr3 and PEA-CsPbBr3 perovskite films; (b) shows the XPS N1s spectra of the micro-region of the reference perovskite film in Comparative Example 1, with the black curve representing the original data and the yellow curve representing the fitted values; (c) shows the XPS N1s spectra of the micro-region of the migration region of the heterojunction sample in Example 1. Detailed Implementation
[0038] To make the objectives, technical solutions, and effects of this invention clearer and more explicit, the invention is further described in detail below. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention.
[0039] Example 1:
[0040] A novel method for preparing lateral 3D / quasi-2D perovskite heterojunctions includes the following steps:
[0041] 1. Preparation of perovskite precursor solution:
[0042] Weigh 32.2 mg of phenylbutyl bromide (PBABr), 9.4 mg of phenylethyl bromide (PEABr), 56.2 mg of lead bromide, and 40.8 mg of cesium bromide into a wash-free bottle using a precision balance, and add 1 mL of DMSO solvent. Heat at 60°C and stir at 600 rpm for at least 6 hours. Cool to room temperature and let stand for half an hour before use.
[0043] 2. Preparation of PVK solution:
[0044] Weigh 14 mg of PVK powder with an average molecular weight of 25,000–50,000 into a wash-free bottle and add 1 mL of chlorobenzene solvent. Heat at 60°C and stir at 600 rpm for at least 6 hours. Cool to room temperature and let stand for half an hour before use.
[0045] 3. Fabrication of quasi-two-dimensional perovskite lateral devices:
[0046] (1) Cleaning of glass substrate: Wipe the ultra-white glass slide (1.3cm×1.3cm) repeatedly with a lint-free cloth soaked in anhydrous ethanol for at least 2 minutes, and then ultrasonically clean it with acetone-water-ethanol for 10 minutes in sequence. Before use, dry the glass slide with nitrogen gas, and then clean it in an ultraviolet ozone treatment machine for 10 minutes.
[0047] (2) Preparation of PVK layer: The ozone-cleaned glass slide was transferred to a glove box under nitrogen atmosphere. The prepared 14 mg / mL PVK solution was spin-coated onto the glass substrate at 2000 rpm for 45 s, and then annealed on a hot plate at 150 °C for 30 min.
[0048] (3) Preparation of quasi-two-dimensional perovskite layer: The prepared perovskite precursor liquid is dropped onto the PVK layer (it needs to be spread evenly by hand), and then spin coating is started. The speed is set to 4000 rpm and the time is 2 min. Then, it is annealed on a hot stage at 100℃ for 30 min.
[0049] (4) Au interdigitated electrode deposition: Place the spin-coated glass slide onto the interdigitated electrode mask and secure it with tape to prevent movement during deposition. Transfer the sample to a vacuum deposition apparatus, setting the thickness to 70 nm and the deposition rate to 0.1 nm / s. The interdigitated electrode width is approximately 100 μm, and the interdigitation distance is 80 μm. After deposition, remove the sample to complete the fabrication process. See [link to quasi-two-dimensional perovskite thin film lateral device structure] for details. Figure 1 As shown.
[0050] (5) Use an excitation intensity of 100mW / cm 2 The lateral device was irradiated with a 405 nm laser, and a bias voltage of 200 V (approximately 1.5 V / μm electric field strength between electrodes) was simultaneously applied to the interdigitated electrodes using a source meter. The irradiation and bias voltage application time was 30 min. The above are the fabrication conditions for the migration interface in the quasi-two-dimensional perovskite thin film lateral device.
[0051] Experimental Analysis: Figure 4 a and b show the changes in PL of the perovskite thin film under illumination and voltage application for 0–3s and 5s–30min, respectively. Figure 4 The results show that, at the beginning of illumination and bias application (1 s), a PL quenching interface appears near the positive electrode of the perovskite film and rapidly migrates towards the negative electrode, reaching the negative electrode at 3 s. When the illumination and bias application time reaches 10 min, a PL quenching interface reappears in the positive electrode region of the perovskite film, also migrating towards the negative electrode. However, the migration rate of this interface is significantly slower than the 0–3 s interface, having migrated only about 40 μm at 30 min.
[0052] The two interfaces have significantly different migration rates, among which Figure 4 The term 'a' represents the halide ion migration process, which is existing technology and will not be elaborated upon here. However... Figure 4 b represents the migration process of ammonium cations.
[0053] Figure 5a is a microscopic fluorescence image of the sample. We call the region in the perovskite film where the PL decreases after the migration interface passes through and is closer to the positive electrode the Migrated Area; and the region where the migration interface has not yet reached the negative electrode and the PL does not change significantly is called the Normal Area.
[0054] To investigate the optical properties of the migration interface, we used micro-region steady-state fluorescence (micro-region PL) to perform single-point measurements of the PL spectra on both sides of the migration interface. For example... Figure 5 As shown in b, the PL peak of the perovskite film exhibits a significant redshift after illumination and bias voltage are applied. (Reference) Figure 2 The photoluminescence (PL) peak of the quasi-two-dimensional perovskite film b is located at 507 nm, indicating a small luminescent center size, and there is a significant n=3 perovskite luminescence signal at ~464 nm. After 30 minutes of illumination and bias voltage, the PL peak in the normal region shifts to 512 nm, a redshift of about 5 nm, indicating a significant increase in the luminescent center size, and a decrease in the intensity of the n=3 luminescence peak. The redshift of the PL peak in the migration region is even more significant, with the emission peak located at 517 nm, a redshift of about 10 nm, approaching the PL peak position (520 nm) of the three-dimensional CsPbBr3 perovskite, and the low-dimensional perovskite luminescence peak of n=3 almost disappears. In the migration region where the interface has been traversed, the n=3 luminescence peak disappears, and the PL peak position approaches that of the three-dimensional perovskite, indicating that the low-dimensional phase fusion in this region is basically complete, and the original quasi-two-dimensional film has transformed into a three-dimensional perovskite.
[0055] To further confirm the crystal structure of the perovskite films on both sides of the migration interface, we used focused ion beam to prepare ultrathin cross-sectional samples at the interface of 3D / quasi-2D perovskite lateral heterojunctions and characterized them using aberration-corrected STEM. Figure 6 Image a shows a cross-sectional STEM image of the heterojunction interface, where the red dashed line represents the migration region, the yellow dashed line represents the normal region, and the white dashed line represents the heterojunction interface. We observed significant differences in the perovskite grain shape between the migration and normal regions. Figure 6 c is a high-resolution STEM cross-sectional image of the normal region, showing that the perovskite film in the normal region consists of stacked layered nanosheets, indicating that the crystal structure in the normal region is still a quasi-two-dimensional perovskite nanosheet structure. However, the quasi-two-dimensional perovskite nanosheet structure disappears in the migration region, replaced by a monolithic perovskite grain. Figure 6 b is a high-resolution STEM image of the perovskite grains in the migration region, showing an almost perfect single-crystal structure with clearly visible atomic images. No layered quasi-two-dimensional structure is observed, indicating that it is a high-quality three-dimensional perovskite grain. Figure 6 The area within the white dashed line represents the heterojunction interface (the region where quasi-two-dimensional perovskite nanosheets transition to three-dimensional perovskite grains). Measurements show that its width is only 9.7 nm, much narrower than the heterojunction widths reported in existing literature.
[0056] In summary, we have gained a clear understanding of the optical properties, surface morphology, and crystal structure of 3D / quasi-2D perovskite lateral dimension heterojunctions. We have confirmed that treating quasi-2D perovskite films with illumination and bias voltage results in a migration interface that slowly moves from the positive to the negative electrode. This migration interface is essentially a heterojunction interface between 3D and quasi-2D perovskite. Microscopic absorption and cross-sectional TEM results show that quasi-2D perovskite nanosheets fuse under illumination and bias voltage, forming high-quality 3D perovskite grains, thus transforming the originally uniform quasi-2D perovskite film into a 3D / quasi-2D perovskite lateral dimension heterojunction.
[0057] We achieved rapid in-situ fabrication of perovskite lateral dimension heterojunctions through light irradiation and bias treatment, which greatly simplifies the fabrication method of perovskite lateral dimension heterojunctions. Furthermore, the formed heterojunction has a clear and sharp junction interface with a width of less than 10 nm, which is the narrowest value in the prior art.
[0058] Example 2:
[0059] The difference from Example 1 is that:
[0060] 1. Preparation of perovskite precursor solution:
[0061] Weigh 32.2 mg of phenylbutyl bromide (PBABr), 56.2 mg of lead bromide, and 40.8 mg of cesium bromide into a wash-free bottle using a precision balance, and add 1 mL of DMSO solvent. Heat at 60°C and stir at 600 rpm for at least 6 hours. Cool to room temperature and let stand for half an hour before use.
[0062] The remaining preparation steps are the same as in Example 1, and will not be repeated here.
[0063] Example 3:
[0064] The difference from Example 1 is that:
[0065] 1. Preparation of perovskite precursor solution:
[0066] Weigh 9.4 mg of phenylethyl bromide (PEABr), 56.2 mg of lead bromide, and 40.8 mg of cesium bromide into a wash-free bottle using a precision balance, and add 1 mL of DMSO solvent. Heat at 60°C and stir at 600 rpm for at least 6 hours. Cool to room temperature and let stand for half an hour before use.
[0067] The remaining preparation steps are the same as in Example 1, and will not be repeated here.
[0068] To further confirm that the perovskite film did not undergo deprotonation during illumination and bias testing, we used micro-area XPS to characterize the elemental valence states of the heterojunction migration region. To determine the N peak position in the reference perovskite film, we first prepared films containing only PBA. + (Example 2) and PEA + The perovskite films of (Example 3) were labeled PBA-CsPbBr3 and PEA-CsPbBr3, respectively, and the N elemental spectra of these two samples were characterized using XPS. Figure 7 As shown in Figure a, the N1s peak positions in the PBA-CsPbBr3 and PEA-CsPbBr3 samples are located at 402.0 eV and 402.2 eV, respectively, corresponding to PBA... + and PEA + China-NH3 + The peak position. The micro-area XPS spectrum of the reference sample in Comparative Example 1 is shown below. Figure 7 As shown in b, its N1s peak is located at 402.1 eV, with no other N signal, indicating that the N element in the reference perovskite film exists only in the form of -NH3. + . Figure 7 c represents the N1s signal in the migration region of the heterojunction sample. The peak area is lower than that of the reference sample, indicating a decrease in N content. The migration region exhibits only one N1s peak at 402.1 eV, identical to the reference sample and the PBA-CsPbBr3 and PEA-CsPbBr3 samples, suggesting that N in the migration region exists only in the form of -NH3. + It exists in ammonium ion form and does not undergo deprotonation (it is deprotonated to an amine, with the nitrogen peak located at 400 eV).
[0069] The above results indicate that during illumination and bias treatment, LOCs in the quasi-two-dimensional perovskite film did not undergo deprotonation. The decrease in N content in the migration region (three-dimensional perovskite) and the formation of 3D / quasi-2D perovskite lateral heterojunctions were solely caused by LOC migration.
[0070] Comparative Example 1:
[0071] A novel method for preparing lateral 3D / quasi-2D perovskite heterojunctions includes the following steps:
[0072] 1. Preparation of perovskite precursor solution:
[0073] Weigh 32.2 mg of phenylbutyl bromide (PBABr), 9.4 mg of phenylethyl bromide (PEABr), 56.2 mg of lead bromide, and 40.8 mg of cesium bromide into a wash-free bottle using a precision balance, and add 1 mL of DMSO solvent. Heat at 60°C and stir at 600 rpm for at least 6 hours. Cool to room temperature and let stand for half an hour before use.
[0074] 2. Preparation of PVK solution:
[0075] Weigh 14 mg of PVK powder with an average molecular weight of 25,000–50,000 into a wash-free bottle and add 1 mL of chlorobenzene solvent. Heat at 60°C and stir at 600 rpm for at least 6 hours. Cool to room temperature and let stand for half an hour before use.
[0076] 3. Fabrication of quasi-two-dimensional perovskite lateral devices:
[0077] (1) Cleaning of glass substrate: Wipe the ultra-white glass slide (1.3cm×1.3cm) repeatedly with a lint-free cloth soaked in anhydrous ethanol for at least 2 minutes, and then ultrasonically clean it with acetone-water-ethanol for 10 minutes in sequence. Before use, dry the glass slide with nitrogen gas, and then clean it in an ultraviolet ozone treatment machine for 10 minutes.
[0078] (2) Preparation of PVK layer: The ozone-cleaned glass slide was transferred to a glove box under nitrogen atmosphere. The prepared 14 mg / mL PVK solution was spin-coated onto the glass substrate at 2000 rpm for 45 s, and then annealed on a hot plate at 150 °C for 30 min.
[0079] (3) Preparation of quasi-two-dimensional perovskite layer: The prepared perovskite precursor liquid is dropped onto the PVK layer (it needs to be spread evenly by hand) and then spin-coating is started. The speed is set to 4000 rpm and the time is 2 min. Then, it is annealed on a hot stage at 100℃ for 30 min to obtain quasi-two-dimensional perovskite film.
[0080] Experimental analysis: The two-dimensional perovskite thin film was characterized by UV-Vis and steady-state PL, yielding the following results: Figure 2 The results are shown. UV absorption spectroscopy characterization results ( Figure 2 a) It can be seen that three exciton absorption peaks were observed in the perovskite film sample, located at 428 nm, 458 nm, and 477 nm, respectively, corresponding to the quasi-two-dimensional low-dimensional phase perovskite with n = 2, 3, and 4, indicating that the prepared perovskite film is mainly composed of a quasi-two-dimensional structure. In addition, the absorption spectrum shows an absorption signal near 500 nm, indicating the presence of trace amounts of large n-value structures (n ≥ 10) in the film. Meanwhile, the PL spectrum peak of the film is located at approximately 507 nm. Figure 2(b) The sample exhibits a significant quantum confinement effect. Furthermore, a satellite peak at ~464 nm is observed and identified as the emission peak of the n=3 phase. The QY of the thin film is approximately 75%.
[0081] like Figure 3 As shown in Figure a, no pores were found in the morphology image, indicating that the perovskite completely covers the substrate. The root mean square (RMS) surface roughness of the perovskite film is 2.8 nm, indicating that the film has excellent flatness. Next, we characterized the structure of the fabricated quasi-two-dimensional perovskite film lateral device. Cross-sectional samples of the perovskite lateral device were prepared using a confocal ion beam processing (FIB) instrument and then transferred to an aberration-corrected scanning transmission electron microscope for observation, as shown in Figure a. Figure 3 The results are shown in b. The Pt deposited on the surface of the lateral device is a protective layer used to protect the sample area during FIB sample preparation. In TEM imaging, the contrast of each layer is mainly related to the atomic number; therefore, the sample structure can be clearly distinguished by the difference in imaging contrast. The TEM cross-sectional image shows that the PVK thickness in the perovskite lateral device is approximately 60 nm, and the perovskite layer thickness is approximately 15 nm. The boundary between the two layers is clear, and the layer interface is smooth.
[0082] In summary, under the influence of light and an electric field, LOCs in the quasi-two-dimensional perovskite film detach from their original potentials and move from the positive electrode to the negative electrode along the direction of the electric field. As the light and bias treatment time increases, the LOC content in the perovskite film at the positive electrode decreases beyond a critical value, making it impossible to maintain the quasi-two-dimensional structure. This leads to the fusion of the quasi-two-dimensional perovskites into three-dimensional perovskite grains. Furthermore, the critical position of this quasi-two-dimensional fusion continuously migrates towards the negative electrode as the LOCs move, thus forming the slowly moving heterojunction interface we observe.
[0083] The present invention has been illustrated with the above embodiments to explain the detailed preparation method of the present invention. However, the present invention is not limited to the above detailed preparation method, that is, it does not mean that the present invention must rely on the above product and detailed preparation method to be implemented. Those skilled in the art should understand that any improvement to the present invention, or the combination or equivalent substitution of the raw materials of the present invention, falls within the protection scope and disclosure scope of the present invention.
Claims
1. A novel method for preparing lateral 3D / quasi-2D perovskite heterostructures, characterized in that, The steps include the following: Step S1: Spin-coat the perovskite precursor solution onto the substrate to form a film, and then place it on a hot stage for annealing and crystallization to form a quasi-two-dimensional perovskite thin film. Step S2: Place the quasi-two-dimensional perovskite film between two metal electrodes, which are connected to an external power source as positive and negative electrodes to construct an electric field. Step S3: Place the quasi-two-dimensional perovskite film in an electric field strength of 0.1-100V / μm and subject it to light treatment to form a lateral 3D / quasi-2D perovskite heterojunction; The chemical formula of the perovskite precursor solution is L m A n-1 M n X 3n+1 ; Wherein, L is a monovalent (m=2) or divalent (m=1) long-chain organic cation; A can be methylammonium (MA+), formamidinium (FA+), or cesium ion (Cs+); M is a divalent cation from Group IV; X represents CI - ,Br - and I - At least one of them; n represents the [MX6] interval between long-chain organic cations. 4- The number of layers of the octahedron, where n = 1 to ∞.
2. The method for preparing a novel lateral 3D / quasi-2D perovskite heterojunction according to claim 1, characterized in that, The illumination conditions in step S3 are as follows: the wavelength of the light source is selected to be smaller than the position of the first exciton absorption peak of the perovskite; the power density of the light source is 1-5000 mW / cm³. 2 .
3. The method for preparing a novel lateral 3D / quasi-2D perovskite heterojunction according to claim 2, characterized in that, In step S3, the quasi-two-dimensional perovskite film is placed in an electric field for at least 10 minutes. Furthermore, the duration of the light treatment must be at least 10 minutes.
4. The method for preparing a novel lateral 3D / quasi-2D perovskite heterojunction according to claim 1, characterized in that, The light source type for the illumination treatment in step 3 is one of the following: laser, mercury lamp, xenon lamp, or LED.
5. The method for preparing a novel lateral 3D / quasi-2D perovskite heterojunction according to claim 3, characterized in that, The electric field strength in step 3 is 1.5 V / μm; the excitation wavelength of the light source for the illumination treatment is 405 nm, and the power density of the light source is 100 mW / cm². 2 .
6. The method for preparing a novel lateral 3D / quasi-2D perovskite heterojunction according to claim 5, characterized in that, The substrate in step 1 includes one of quartz, PEDOT:PSS, and PVK.
7. The method for preparing a novel lateral 3D / quasi-2D perovskite heterojunction according to claim 1, characterized in that, The long-chain organic cations include one of the following: decaalkylammonium cation, dodecylammonium cation, tetradecylammonium cation, octadecylammonium cation, phenethylammonium cation, phenylbutylammonium cation, and butylammonium cation.
8. The method for preparing a novel lateral 3D / quasi-2D perovskite heterojunction according to claim 1, characterized in that, The 3D / quasi-2D perovskite heterojunction has a clear and sharp junction interface with a width of less than 10 nm.
9. A method for preparing a novel lateral 3D / quasi-2D perovskite heterojunction according to any one of claims 1-8, characterized in that, The preparation method is a one-step in-situ preparation method under light and electric field treatment conditions.
10. The method for preparing a novel lateral 3D / quasi-2D perovskite heterojunction according to claim 9, characterized in that, Under illumination and electric field conditions, the LOCs in the quasi-two-dimensional perovskite film did not undergo deprotonation, and the formation of 3D / quasi-2D perovskite lateral heterojunctions was solely due to LOC migration.